2018
DOI: 10.1002/cmdc.201800474
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)–Coumarin–Caffeine‐Based Complexes as New Potential Anti‐Inflammatory and Anticancer Trackable Agents

Abstract: Three new gold(I)-coumarin-based trackable therapeutic complexes and two non-trackable analogues have been synthesised and fully characterised. They all display anti-proliferative properties on several types of cancer cell lines, including those of colon, breast, and prostate. Two complexes displayed significant anti-inflammatory effects; one displayed pro-inflammatory behaviour; this highlights the impact of the position of the fluorophore on the caffeine scaffold. Additionally, the three coumarin derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Several gold(I) complexes bearing coumarin units were described. [28,47,49] For example gold(I) carbene complex H displayed poor photophysical properties (fluorescence quantum yield, Φ F = 2 %), the fluorescence quenching being attributed to a photo-induced electron transfer between the coumarin and the carbene. [47] Nevertheless fluorescence confocal microscopy demonstrated the uptake of H in the nuclei of A2780 (human ovarian cancer) cells (IC 50 = 12 μM) at a concentration of 50 μM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several gold(I) complexes bearing coumarin units were described. [28,47,49] For example gold(I) carbene complex H displayed poor photophysical properties (fluorescence quantum yield, Φ F = 2 %), the fluorescence quenching being attributed to a photo-induced electron transfer between the coumarin and the carbene. [47] Nevertheless fluorescence confocal microscopy demonstrated the uptake of H in the nuclei of A2780 (human ovarian cancer) cells (IC 50 = 12 μM) at a concentration of 50 μM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fluorescence intensity of the coumarin moiety was reduced by 90 % in this conjugate, thus no microscopy studies on cellular uptake were reported. Several gold(I) complexes bearing coumarin units were described . For example gold(I) carbene complex H displayed poor photophysical properties (fluorescence quantum yield, Φ F =2 %), the fluorescence quenching being attributed to a photo‐induced electron transfer between the coumarin and the carbene .…”
Section: Introductionmentioning
confidence: 99%
“…14 Gold(I) complexes were extensively studied by many researchers including our group. [15][16][17][18][19][20][21][22][23][24][25][26] Contrary to platinum derivatives, the main hypothesis concerning the mechanism of action of gold(I)-based phosphine complexes is the inhibition of thio and/or seleno-cysteine enzymes, such as thioredoxine reductases (TrxRs), via the coordination of gold center to thiols or selenols. TrxRs are in charge of the regulation of oxidative stress and their inhibition leads to the increase of ROS and to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it also presents interesting biological properties, either as an antibacterial or anti-inflammatory agent. [54][55][56][57][58] This last property is interesting because gold(I) complexes often also have anti-inflammatory properties. Knowing that some anticancer treatments induce inflammation phenomena which seem to be the cause of side effects, [59,60] the development of a drug with an anti-inflammatory effect should make it possible to limit such issues.…”
Section: Introductionmentioning
confidence: 99%